Altmetric analysis of third molar surgery (Research, Society and Development, 2022)
Objectives: We are surrounded by a huge amount of data, and it is problematic to assimilate this huge amount of data and convert it into knowledge. This study is intended to provide a guide for compiling an exemplary list of the top articles relevant to third molar surgery according to altmetric analysis. Methods: A bibliographic search (retrospective study) was performed on the Dimensions app with the scheme ("third molar" surgery) in the title, abstract and keyword. The number of citations, altmetric attention score and journal of publication were ranked and analyzed through Microsoft Excel. Tables and graphics were generated to enable data visualization. A graphical illustration of keywords was produced using VOSviewer. Results: A useful list of the top 50 articles was created. There are some notable facts such as the increasing interest in alternative therapies to analgesia for third molar surgery, with a 95% confidence interval (p < 0.05). Some curiosities have been discussed as the increasing interest in surgical methods such as coronectomy and piezosurgery. Conclusions: In addition to the bibliometric analysis, the altmetric analysis is a new, web-based, valuable approach to scientific updating. Both are complementary analyzes. Altmetrics is a great way to update yourself.